A cross-sectional study to determine the use of alternative medicines during pregnancy in the district hospitals in Manicaland, Zimbabwe - Dimene, Liphapang; Mutseyekwa, Fadzai; Chifamba, Jephat; Nyakatawa, Gerald; Mahachi, Carol; Marume, Amos; Bhebhe, Michael; Taderera, Tafadzwa (2020)
Background: Traditional medicines are widely used in the rapidly growing health system and are of economic importance. The study aimed at determining the frequency, pattern of use and factors that influence traditional medicines use during pregnancy.